Analisis Metode Active Debate dalam Peningkatan Hasil Belajar IPS Materi Kenampakan Alam Buatan dan Alami pada Siswa Kelas V SD Negeri 1 Krajan Pekuncen Banyumas - Priambodo, Adityo Rian; Ningsih, Tutuk (ANWARUL, 2025)
This research is motivated by the learning outcomes in social studies lessons and the number of teachers who teach with monotonous learning methods. The purpose is to analyze the effectiveness of the Active Debate method in improving student learning outcomes in Social Sciences (IPS) subjects, especially in the material Appearance of Artificial and Natural Nature. The Active Debate method was chosen for its ability to increase students' active involvement in the learning process, which is expected to deepen their understanding of the material. The research method in this study is qualitative descriptive, data collection without setting from the researcher, by carrying out observations, interviews and documentation in data collection using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) method approach to analyze strengths, weaknesses, opportunities, and threats in the application of this method. The results of the study show that the Active Debate method has succeeded in improving learning outcomes and student participation, developing critical thinking skills, and improving students' understanding of the material. The conclusion of this study is that the Active Debate method can be one of the alternatives used by teachers to improve social studies learning outcomes of students as well as develop critical thinking skills, and improve students' understanding of artificial and natural appearance materials in students. This research is expected to have implications for the development of more interactive and effective learning methods in improving student learning outcomes in social studies subjects.